Diseño de un regulador de corriente eléctrica para las bobinas modulares del Stellarator SCR-1 - Mora, Jaime (2017)
The stellarator of Costa Rica 1 (SCR-1) is a magnetic confinement device for high temperature plasma, designed, built and in implementation in the Costa Rica Institute of Technology. During operation, the plasma will be confined by the magnetic field (~43,8 mT) of 12 coils with six loops of copper wire AWG #4, and fed by a battery bank (150 Ah, 120 V) that should provide a constant current of 767,8 A for a period of 4 s to 10 s. The change of electric resistance made by the ohmic heating in the wire required to design, build and implement a current regulator that would supply a constant current of 767,8 A during the indicated period. This article presents the design of an electric circuit, powerful and low-cost, to regulate the electric current in the modular coils of the SCR-1. Additionally, it describes the design of the digital control of the electric circuit PID, with a velocity algorithm that decreases the magnitude of the harmonics to avoid issues within the magnetic field of the stellarator.